Symbolic Meaning, Social Culture, and Benefit on Economic Tanimbar Woven Fabric - Swekan, Max Wa; Kanto, Sanggar; Wisadirana, Darsono; Susilo, Edi (Technium Social Sciences Journal, 2023)
West Southeast Maluku Regency / Tanimbar Islands, Maluku Province also has local wisdom that has been passed down from generation to generation, namely the Ikat Weaving Fabric, which is better known as "Tanimbar Fabric". This study aims to find the symbolic and social, cultural, and economic meaning behind the Tanimbar Ikat Weaving Fabric. This study uses a qualitative descriptive method with an ethnographic approach, and a sociological method with a social facts paradigm approach. The findings of this study from a symbolic aspect illustrate that Tanimbar Fabrics are usually passed down through life skills or skills from a mother or adult woman to her daughter, or young woman by seeing the way her mother weaves every day, which is done traditionally. The social aspect has certain meanings in the life of the Tanimbar community which positions women in a high social status. The economic aspect is that this cloth business, if occupied, provides additional potential income. So that optimal efforts are needed in the empowerment of Tanimbar Fabrics both from the symbolic, social, and economic aspects impact on wellbeing. The step is that the process for making and processing Tanibar woven fabrics is sought to be faster and cheaper.